(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
It is projected that E-Commerce will grow to be a massive sector in the next years as it hascaptured the interest and minds of customers across the globe like never before. Globalization and marketliberalization, on the other hand, make it difficult for international tax arrangements to keep up with thesechanges. A new business model has arisen based on the use of seamless, cross-border cyber networks.For company methods based on real-time management and using cutting-edge technology, E-Commercehas created a distinctive code of conduct. It would be difficult to create an effective tax policy without athorough knowledge of the sector, taxation authorities’ issues, and Internet-specific quirks. It argues thatE-Commerce has grown tremendously over the globe including in India, and that legal and tax issueshave arisen as a result of this expansion. Indian tax reform is also taken into consideration in thisresearch, which aims to keep up with India’s explosive development in E-Commerce.